2022
DOI: 10.3233/wor-205140
|View full text |Cite
|
Sign up to set email alerts
|

Association between Whole-Body Vibration exposure and musculoskeletal disorders among dumper operators: A case-control study in Indian iron ore mines

Abstract: BACKGROUND: Dumper operators in mines worldwide are subjected to Musculoskeletal Disorders (MSDs) due to whole-body vibration exposure. This study evaluated the working-life-Whole-Body Vibration (WBV)-exposure and their association with various MSDs among dumper operators in mines which remains poorly addressed. METHODS: This case-control study in Indian iron ore mines was conducted to compare randomly selected 65 dumper operators and 65 office workers. Data were collected through face-to-face interviews using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…A study on dump truck operators in an Indian Iron ore mine showed that every day the majority of the operators in the study (59%) were exposed to vibrations exceeding the lower limit (0.45 m•s −2 ) stated by ISO-2631. The effect of high WBV includes risk of back pain, knee pain, leg pain and musculoskeletal disorders [1]. Another study measured vibration transmitted to a tractor seat on different speeds and road types and showed that ISO limits are exceeded in multiple common farming conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A study on dump truck operators in an Indian Iron ore mine showed that every day the majority of the operators in the study (59%) were exposed to vibrations exceeding the lower limit (0.45 m•s −2 ) stated by ISO-2631. The effect of high WBV includes risk of back pain, knee pain, leg pain and musculoskeletal disorders [1]. Another study measured vibration transmitted to a tractor seat on different speeds and road types and showed that ISO limits are exceeded in multiple common farming conditions.…”
Section: Introductionmentioning
confidence: 99%